Characterization of Enterobacter cloacae complex clinical isolates: comparative genomics and the role of the efflux pump AcrAB-TolC over-expression and NDM-1 production - Jiang, Nan; Pu, Faxiao; Wang, Wenji; Wang, Dongguo; He, Jiayu (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundCarbapenem-resistant Enterobacter cloacae complex (ECC) has emerged as the third most prevalent nosocomial Enterobacterales pathogen, propelled by the synergy between intrinsic defenses, e.g. AcrAB-TolC efflux pump overexpression and horizontally acquired determinants such as the plasmid-borne blaNDM-1.MethodsOur study employed a comprehensive, multi-faceted strategy to characterize three carbapenem-resistant, NDM-1-positive ECC isolates, named x9, F12, and x230151. The integrated methodology merged phenotypic antimicrobial susceptibility testing with functional conjugation and electroporation assays. High-resolution hybrid Nanopore-Illumina genome assemblies enabled detailed genomic annotation and extensive resistance profiling. We further quantified acrAB-tolC efflux pump expression via quantitative RT-PCR and reconstructed the evolutionary history of the blaNDM-1-bleMBL module using comparative plasmid genomics.ResultsAll three ECC isolates were extensively Drug-Resistant (XDR) with carbapenem MICs ≥ 8 mg/L. Genomes carried 33–35 resistance loci, including > 5-fold up-regulated acrAB-tolC on chromosome, and constitutive chromosomal expression of blaACT-type AmpC further blunted the activity of cephalosporins and carbapenems. The blaNDM-1-bleMBL resided on 110–240 kb IncF/IncN/IncX3 plasmids that transferred at 3-8×10–3 per donor and were embedded in Tn125/Tn3000 transposons flanked by ISAba125/IS26. These replicons also carried ESBLs (blaCTX-M-15), blaTEM-1, aminoglycoside- modifying enzymes (armA, aadA1) and intact class 1 integrons (In2, In799 and In1465). Despite>90% backbone identity of the blaNDM-1-bleMBL, the module could be reversibly excised, inverted or truncated, allowing rapid “gene-offload” and re-acquisition under shifting antibiotic pressure.ConclusionOnce the carbapenem MIC surpassed 8 mg/L, the tandem action of the chromosomally over-expressed AcrAB-TolC efflux pump and plasmid-borne blaNDM-1 carbapenemase rendered ECC virtually untreatable. Mutations in ramR and soxR regulators, as well as promoter insertions or deletions that amplify either system should also be tracked in real-time via sustained surveillance.Effective containment would require combination strategies that simultaneously inhibit efflux, neutralize β-lactamase activity, and destabilized or eliminated the IncF/IncN/IncX3 plasmids carrying blaNDM-1.